Clinically significant reduction of persistent late-onset auditory verbal hallucinations with adjunctive repetitive transcranial magnetic stimulation: A case report - Macedo Mustafé, Gustavo; Pelletier-De Koninck, Béatrice; Brodeur, Sébastien; Boivin-Lafleur, David; Arrouet, Alana; Laureys, Steven; Hoyer, Roxane; Roy, Olivier (Santé mentale au Québec, 2026)
Late-onset auditory verbal hallucinations (AVH) present diagnostic and therapeutic challenges, particularly when antipsychotic treatment is limited by poor tolerability. We report a case of a 75-year-old woman with de novo AVH temporally related to hemp oil use, in the general context of longstanding hearing impairment. Symptoms persisted and progressively worsened over 12 months despite discontinuation and antipsychotic treatment, resulting in marked distress and functional impairment. Adjunctive repetitive transcranial magnetic stimulation (rTMS) targeting the left temporoparietal cortex was administered in 2 separate treatment courses. Each course was associated with a marked reduction in AVH severity and enabled substantial tapering of antipsychotic medication. In both instances, symptom relapse occurred within 2-3 months after rTMS discontinuation. This case highlights the multifactorial nature of late-onset AVH and suggests that rTMS may serve as a time-limited, adjunctive intervention in selected older patients when pharmacological strategies are constrained, with potential implications for maintenance-based approaches.